Verdi and the French aesthetic : verse, stanza, and melody in nineteenth-century opera - Giger, Andreas (Cambridge University Press, 2008)
Focusing on Verdi's French operas, Giger shows how the composer acquired an ever better understanding of the various approaches to French versification while gradually bringing his works in line with French melodic aesthetic. In his first French opera, Jérusalem, Verdi treated the text in an overly cautious manner, trying to avoid prosodic mistakes; in Les Vêpres siciliennes he began to apply more freedom, scanning the verses against some prosodic accents to convey the lightheartedness of a melody; and in Don Carlos he finally drew on the entire palette of prosodic interpretations. Most of Verdi's melodic accomplishments in the French operas carried over into the subsequent Italian ones, setting the stage for what later would be called operatic verismo. Drawing attention to the significance of the libretto for the development of nineteenth-century French and Italian opera, this text illustrates Verdi's gradual mastery of the challenges he faced, and their historical significance.
Keywords: Verdi, Giuseppe, : 1813-1901 : Criticism and interpretation; Opera : Italy : 19th century; Opera : France : 19th century; Music : Philosophy and aesthetics